Hard-to-Abate Sectors: The role of industrial carbon capture and storage (CCS) in emission mitigation. (15th October 2021) - Paltsev, Sergey; Morris, Jennifer; Kheshgi, Haroon; Herzog, Howard
Highlights: Carbon capture can mitigate both process and energy-related industry emissions. Low-emission cement production is particularly dependent on carbon capture. Global emission mitigation costs are substantially higher without industrial CCS. Advanced options (e.g., cryogenic capture) offer pathways for CCS expansion. Pathways to industrial CCS deployment all rely on support from sustained policies. Abstract: Carbon capture and storage (CCS) technology is an important option in the portfolio of emission mitigation solutions in scenarios that lead to deep reductions in greenhouse gas (GHG) emissions. We focus on CCS application in hard-to-abate sectors (cement industry, iron and steel, chemicals) and introduce industrial CCS options into the MIT Economic Projection and Policy Analysis (EPPA) model, a global multi-region multi-sector energy-economic model that provides a basis for the analysis of long-term energy deployment. We use the EPPA model to explore the potential for industrial CCS in different parts of the world, under the assumptions that CCS is the only mitigation option for deep GHG emission reductions in industry and that negative emission options are not available for other sectors of the economy. We evaluate CCS deployment in a scenario that limits the increase in average global surface temperature to 2 °C above preindustrial levels. When industrial CCS is not available, global costs of reaching the target are higher by 12% in 2075 and 71% in 2100 relative to the cost of achieving the policy with CCS. Overall, industrial CCS enables continued growth in the use of energy-intensive goods along with large reductions in global and sectoral emissions. We find that in scenarios with stringent climate policy, CCS in the industry sector is a key mitigation option, and our approach provides a path to projecting the deployment of industrial CCS across industries and regions.